. Adoption Value of serum Hematological Inflammatory Markers in Early Diagnosis of Necrotizing Enterocolitis : Inflammatory Markers in NEC Diagnosis - Zhang, Pengfei (Journal of Medical Biochemistry, 2024)
Introduction: early diagnosis and intervention of neonatal necrotizing enterocolitis (NEC) are crucial for improving prognosis. It was to assess the diagnostic and staging value of high-sensitivity C-reactive protein (hs-CRP), white blood cell count (WBC), and interleukin (IL)-6 levels in NEC, and to explore their correlation with disease severity. Materials and Methods: this retrospective study analyzed clinical data from 43 NEC patients in the neonatology department of Northwest Women and Children’s Hospital, designated as the experimental group (EG), and concurrently selected 38 healthy newborns as the control group (CG). Serum hs-CRP, WBC, and IL-6 were measured in both groups. Statistical analyses were performed using SPSS 27.0. Results: hs-CRP, WBC, and IL-6 in NEC patients greatly surpassed those in healthy newborns, and these markers were notably positively correlated with NEC staging (r=0.756, 0.234, 0.901, P<0.05). Combined detection of hs-CRP, WBC, and IL-6 in early NEC diagnosis yielded an AUC of 0.988, with a sensitivity of 93.02% and specificity of 97.37%, all superior to individual detections (P<0.05). Conclusion: hs-CRP, WBC, and IL-6 have important value in diagnosis and assessment of NEC, particularly the combined detection which greatly improves early diagnostic accuracy. Future research should further investigate additional inflammatory markers to optimize diagnostic methods, providing a more comprehensive scientific basis for early clinical intervention and treatment.